2018
DOI: 10.1111/psyp.13213
|View full text |Cite
|
Sign up to set email alerts
|

ERP correlates of valence asymmetry during incentive anticipation

Abstract: The stimulus-preceding negativity (SPN) is a reliable index of incentive anticipation. However, it remains controversial whether the anticipatory process indexed by the SPN is modulated by incentive valence. The present study investigated the effect of valence on the SPN in a gambling task that required participants to make a binary (gain vs. loss) prediction after their choice on trials with different reward probabilities. Behaviorally, the participants exhibited a positive bias in their prediction. Electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The relation of valence to SPN is not well understood (discussed in Brunia et al, ; Ohgami et al, ). When expected gain and loss conditions are directly compared, results show either equally large SPNs (Angus et al, ; Donkers, Niewenhuis, & van Boxtel, ; Zheng et al, ), larger ones in certain conditions with expected gain (Li et al, ; Zhang et al, ; Zheng, Li, Wang, Wu, & Liu, ), or a relative topographical shift toward the left hemisphere for potential gain contexts (Ohgami et al, ). No study has reported larger SPN amplitudes in a loss than gain context, to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The relation of valence to SPN is not well understood (discussed in Brunia et al, ; Ohgami et al, ). When expected gain and loss conditions are directly compared, results show either equally large SPNs (Angus et al, ; Donkers, Niewenhuis, & van Boxtel, ; Zheng et al, ), larger ones in certain conditions with expected gain (Li et al, ; Zhang et al, ; Zheng, Li, Wang, Wu, & Liu, ), or a relative topographical shift toward the left hemisphere for potential gain contexts (Ohgami et al, ). No study has reported larger SPN amplitudes in a loss than gain context, to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Data reported in Experiment 1 are from the nonoverlapping results of our previous study (Li et al, 2018 ) during which we analyzed EEG signals during the anticipatory phase of a reward prediction task. Here, we analyzed EEG signals in response to feedback processing of the task.…”
Section: Methodsmentioning
confidence: 99%
“…Clarity and transparency are not only rewarding, they are key ingredients for organizational performance (Gartenberg, Andrea, & George, 2016). Uncertainty and ambiguity create varying degrees of threat response (Chew, Ebstein, & Zhong, 2012; Kapp, Whalen, Supple, & Pascoe, 1992), depending upon the situation and the person (Tanovic, Gee, & Joormann, 2018), leading to increased levels of anxiety (de Berker et al, 2016) and stress (de Berker et al, 2016), negativity, and perceptions of pain—be it physical (e.g., Ma, Qiu, Fu, & Sun, 2018; Tanovic, Gee, & Joormann, 2018) or social (Li et al, 2018).…”
Section: Using the Connect© Model In Consulting Psychologymentioning
confidence: 99%